Empirical Selection of Auroral Kilometric Radiation During a Multipoint Remote Observation With Wind and Cassini. Issue 10 (18th October 2021) - Waters, J. E.; Jackman, C. M.; Lamy, L.; Cecconi, B.; Whiter, D. K.; Bonnin, X.; Issautier, K.; Fogg, A. R.
Abstract: Auroral Kilometric Radiation (AKR) is terrestrial radio emission that originates in particle acceleration regions along magnetic field lines, coinciding with discrete auroral arcs. AKR viewing geometry is complex due to the confinement of the source regions to nightside local times (LTs) and the anisotropy of the beaming pattern, so observations are highly dependent on spacecraft viewing position. We present a novel, empirical technique that selects AKR emission from observations made with the spin‐axis aligned antenna of the Wind/WAVES instrument, based on the rapidly varying amplitude of AKR across spacecraft spin timescales. We apply the technique to Wind/WAVES data during 1999 day of year 227–257, when the Cassini spacecraft flew past Earth and provided an opportunity to observe AKR from two remote locations. We examine the AKR flux and power, with observations made from LTs of 1700–0300 hr having an average power up to 10 4 Wsr ‐1 larger than those on the dayside and an increasing AKR power observed at higher magnetic latitudes. We perform a linear cross‐correlation between the Wind AKR power and the spacecraft magnetic latitude, showing positive then negative correlation as Wind travels from the Northern to Southern magnetic hemisphere. Statistically significant diurnal modulations are found in the whole 30‐day period and in subsets of the data covering different local time sectors, indicative of a predominantly geometrical effect for remote AKR viewing. The reproduction of well‐known features of the AKR verifies the empirical selection and shows the promise of its application to Wind/WAVES observations. Plain Language Summary: Auroral Kilometric Radiation (AKR) is naturally occurring radio emission from the Earth's Northern and Southern polar regions, which becomes more intense as the aurora brightens. In this work, we examine data from the Wind spacecraft WAVES instrument from a 30‐ day interval in 1999 when a second spacecraft, Cassini, was also flying near Earth and measuring the AKR from a different viewpoint. In this work, we select the AKR using an empirical measure of the variability observed by the WAVES instrument, and compare the distribution and time profile of AKR intensity. Comparing measurements of this radio emission from different spacecraft positions help us to understand how the AKR is best viewed and illustrate the constrained beaming of the emission. This information is important for anyone wanting to attempt to interpret measurements of the AKR. Key Points: Novel, empirically based method to extract Auroral Kilometric Radiation (AKR) from Wind/WAVES is presented and applied to observations made during the Cassini flyby Selected data show a distribution of AKR power with expected longitudinal and latitudinal visibility constraints Diurnal temporal modulation observed, suggesting the dominance of a geometric viewing effect and agreeing with previous AKR observations